Local Realistic Interpretation of Entangled Photon Pairs in the Weyl-Wigner Formalism - Santos, Emilio (Frontiers in Physics, 2020)
A polarization correlation experiment with two maximally entangled photons created by spontaneous parametric down-conversion is studied in the Weyl-Wigner formalism, that reproduces the quantum predictions. A realistic stochastic interpretation is proposed suggesting that an analysis of the experiments more detailed than the Bell approach may be compatible with local realism. Entanglement appears as a correlation between fluctuations of signal and vacuum fields.